HUBUNGAN DUKUNGAN KELUARGA DENGAN SELF EFFICACY PADA LANSIA PENDERITA STROKE - Desi Nindya Kirana; Linda Suryani (Universitas Batam, 2022)
Stroke is a functional brain disorder due to disruption of blood supply or blood flow due to blockage or bleeding that results in neurological deficits. Neurological deficit in which there is abnormal function in the area of ​​the body due to the distribution of brain function, spinal cord, peripheral nerves and muscles resulting in an inability to carry out daily activities. Self-efficacy is needed by stroke patients to be able to perform activities optimally. One of the factors to increase self-efficacy is the need for family support. The condition of the Covid-19 pandemic has greatly impacted the mental and mental health of stroke patients, especially the elderly. The purpose of this study was to determine the relationship between family support and self-efficacy of stroke patients during the Covid-19 pandemic. Methods: This research is quantitative. This research was conducted in the work area of ​​Simpang Tiga Health Center Pekanbaru. The number of respondents 46 people with stroke. The research design is cross sectional using a Likert scale questionnaire research instrument. The analysis used is the chi-square statistical test frequency distribution. The results of this study concluded that there was a significant relationship between family support and self-efficacy of stroke patients (p value 0.002 ; = 0.05). Recommendation: This study recommends that health workers, both nurses, midwives, can provide counseling to families of stroke patients about the importance of support